Hydrodynamics of a Fluid Catalytic Cracking Stripper Using γ-ray Densitometry - Veluswamy, Ganesh; Upadhyay, R.; Utikar, Ranjeet; Evans, G.; Tade, Moses; Glenny, M.; Roy, S.; Pareek, Vishnu (American Chemical Society, 2011)
This paper reports hydrodynamics of a laboratory-scale fluid catalytic cracking (FCC) stripper. The laboratory-scale stripper was designed by geometrically and dynamically scaling down an industrial-scale FCC stripper that had a disk and donut baffle. The solids holdup was measured using a γ-ray densitometry technique with a 3-μCi-strength Cs-137 radioactive source. Measurements were taken at different elevations and chordal positions. The effect of operating conditions on the solids holdup profiles was investigated in detail. For example, the particle flow rate was varied from 0.025 kg/s to 0.042 kg/s, and the superficial air velocity between 0.74 m/s and 1.1 m/s. It was observed that the shape of baffles played an important role in the hydrodynamics of the stripper. Several dead zones were noticed under the baffle regions indicating unused areas in the stripper. The measured solid holdup radial profiles were of asymmetric nature underlying the need for three-dimensional (3D) simulations. At low superficial gas velocities, there was a widespread segregation in the solid phase, which along with the solid holdup decreased on increasing the air superficial velocity. However, the change in solid flow rates did not have any effect on the solids holdup.